2017
DOI: 10.1177/0018720817712597
|View full text |Cite
|
Sign up to set email alerts
|

Ergonomic Benefits From a Laparoscopic Instrument With Rotatable Handle Piece Depend on the Area of the Operating Field and Working Height

Abstract: Objective To evaluate the effect of a laparoscopic instrument with a 360° rotatable handle piece (rot-HP) on biomechanical stress and precision in different areas of a simulated operating field at two working heights. Background Surgeons performing laparoscopic procedures are exposed to biomechanical stress and have an increased risk of musculoskeletal complaints. Method Fifty-seven healthy subjects (27 men, median age 26) without experience in laparoscopy performed a precision task in four quadrants (A-D) of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
9
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 37 publications
1
9
0
Order By: Relevance
“…The results showed that the PF prototype increased the amount of time in neutral position during the experiment, especially in arm abduction, where the participants keep their arm position in neutral ranges 91,7% of the time (Table 5). This is an interesting results because the arm abduction movement is considered critic in laparoscopic surgery [19], [21], [37], [75], [76] and difficult to improve because of the practice [151]. The results obtained with the control instrument in the simulation task are consistent with the arm abduction results presented by previous literature during real procedures [76] being the results in real practice slightly worse probably due to the tension inherent to a real procedure.…”
Section: Discussionsupporting
confidence: 86%
See 2 more Smart Citations
“…The results showed that the PF prototype increased the amount of time in neutral position during the experiment, especially in arm abduction, where the participants keep their arm position in neutral ranges 91,7% of the time (Table 5). This is an interesting results because the arm abduction movement is considered critic in laparoscopic surgery [19], [21], [37], [75], [76] and difficult to improve because of the practice [151]. The results obtained with the control instrument in the simulation task are consistent with the arm abduction results presented by previous literature during real procedures [76] being the results in real practice slightly worse probably due to the tension inherent to a real procedure.…”
Section: Discussionsupporting
confidence: 86%
“…The fact that they did not find significant differences between the angles 40° and 80° can be caused because each surgeon have their own optimal handle-to-shaft angle, and the use of the PF could be an effective solution to increase the comfort of the surgeons. In 2007, an study evaluating a rotatable instrument that can rotate 360° transversely to the shaft of the handle [151]. According the authors, the rotatable instrument allows some reductions of muscular activity in biceps and flexor carpi radials but they did not found these reductions on trapezius and deltoids.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…To follow these studies, mMA value was used as an objective parameter to evaluate the ergonomic impact of grip design on targeted muscle during NPE, in this study. However, the sEMG value at the maximum voluntary contraction is often recorded as a reference value of a targeted muscle, to utilize the normalized sEMG value as a parameter to evaluate the level of muscle fatigue 6‐8,14 . Furthermore, a self‐reported questionnaire has been also used as a subjective parameter to evaluate ergonomic environment surrounding surgeons 13,14 .…”
Section: Discussionmentioning
confidence: 99%
“…Ergonomic analyses are widely applied today to workplace and tool design in the industry, 1,2 military, 3 sports, 4 and medicine 5 . Recently, multiple studies reported ergonomic benefits in the field of medical endoscopy, for example, laparoscopy 6,7 and ureteroscopy 8 . These reports highlighted that it is important to understand the biomechanical stress on physicians during endoscopy to identify the factors that may contribute to fatigue and discomfort related to daily clinical practice.…”
Section: Introductionmentioning
confidence: 99%